1993
DOI: 10.1042/bj2900633
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear diacylglycerol is increased during cell proliferation in vivo

Abstract: Highly purified nuclei were prepared from livers and kidneys of rats undergoing compensatory hepatic or renal growth, the former being predominantly by cellular proliferation, and the latter mostly by cellular enlargement. In liver, an increase in nuclear diacylglycerol (DAG) concentration occurred between 16 and 30 h, peaking at around 20 h. At the peak of nuclear DAG production a specific translocation of protein kinase C to the nucleus could be detected; no such changes occurred in kidney. There was no dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 24 publications
(36 reference statements)
6
79
0
1
Order By: Relevance
“…5). Increased production of nuclear DG upon cell stimulation has been detected in many cells [30,31], and the importance of the nuclear localization of protein kinases C has been addressed [32]. It is thus likely that DGKc~ is the isozyme participating in the metabolic processing of nuclear DG.…”
Section: Resultsmentioning
confidence: 99%
“…5). Increased production of nuclear DG upon cell stimulation has been detected in many cells [30,31], and the importance of the nuclear localization of protein kinases C has been addressed [32]. It is thus likely that DGKc~ is the isozyme participating in the metabolic processing of nuclear DG.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the data collected to date by ourselves and others [5][6][7]9] have utilized nuclei that have been stripped of their envelopes by detergents. Moreover, we have so far assumed that nuclear inositides are the major source of the DAG generated in this location, which in turn probably serves to recruit protein kinase C to the nucleus [5] and activate it.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the relative contribution of the nuclear envelope to nuclear inositide metabolism remains to be elucidated. Most studies of inositol lipids involving nuclei have required removal of the nuclear envelope before lipid analysis [5][6][7]. However, when Jarpe et al [8] investigated the source of DAG generated from isolated, entirely intact nuclei, they concluded that phosphatidylcholine, rather than inositides, was the primary source.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear phospholipase C-β 1 IGF-mediated PtdIns(4,5)P 2 hydrolysis and DAG generation in membrane-depleted nuclei of Swiss 3T3 cells pointed to the possible involvement of phospholipase C (20), and the activation of the nuclear PI-PLC-β 1 in response to IGF-I was later confirmed (46,47). In vivo model of regenerating rat liver showed the similar increase in the level of the nuclear DAG 20 hours after partial hepatectomy (5). The early immunoanalysis of isolated rat liver nuclei for the presence of various PI-PLC isoforms demonstrated the nuclear presence of PI-PLC-β 1 (21).…”
Section: Nuclear Phospholipase Cmentioning
confidence: 76%
“…In addition to providing the survival signal in PC12 cells, the nuclear PI3K class I activation and PtdIns (3,4,5 …”
Section: Nuclear Pi 3-kinase In Myeloid Differentiationmentioning
confidence: 99%